A Voluminous Right Atrial Myxoma Revealed by Right Side Heart Failure. Issue 3 (10th December 2012) - Nazzi, Mbarek; Belhachmi, Hassan; Badidi, Mehdi; Zbir, Elmehdi; Mohty, Dania
Mini‐Abstract Right atrial myxoma is rare. Its clinical presentation is polymorphic. The most common presentation is heart failure, but could be pulmonary embolism or tricuspid valve obstruction. We report here, the case of a 60‐year‐old man admitted for severe heart failure. The echocardiogram showed a voluminous and floating right atrial mass, appending to the interatrial septum and protruding into the right ventricle causing severe tricuspid regurgitation. Chest computed tomography scan demonstrated multiple distal pulmonary emboli. Surgical excision and tricuspid annuloplasty were successfully performed. Histological findings were typical of a benign myxoma. At follow‐up, there was a complete regression of heart failure signs.